2018
DOI: 10.3892/ijmm.2018.3894
|View full text |Cite
|
Sign up to set email alerts
|

SFMBT2 positively regulates SOX9 and chondrocyte proliferation

Abstract: SRY-box 9 (SOX9) is the master regulator of the chondrocyte phenotype, which is essential for differentiating chondrogenic mesenchymal condensations into chondrocytes, and is involved in regulating every stage of chondrocyte differentiation. SOX9 deletion in chondrocytes at the late stages of cartilage development results in decreased chondrocyte proliferation; inhibited expression of cartilage matrix genes, including Indian hedgehog and the downstream parathyroid hormone-related protein; and premature convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…SOX9 is a master transcription factor that is essential for chondrogenic differentiation and development from MSCs [57]. Its expression is high in mitotic and early prehypertrophic chondrocytes, but downregulated in hypertrophic chondrocytes [42,58]. In this study, we confirmed that during the 21-day chondrogenic differentiation, SOX9 expression was significantly upregulated at day 7 and was maintained at a high level, with an expression pattern similar to that of COL2.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…SOX9 is a master transcription factor that is essential for chondrogenic differentiation and development from MSCs [57]. Its expression is high in mitotic and early prehypertrophic chondrocytes, but downregulated in hypertrophic chondrocytes [42,58]. In this study, we confirmed that during the 21-day chondrogenic differentiation, SOX9 expression was significantly upregulated at day 7 and was maintained at a high level, with an expression pattern similar to that of COL2.…”
Section: Discussionsupporting
confidence: 77%
“…SOX9 is a negative regulator of chondrocyte hypertrophic differentiation [42], and the β-catenin pathway is involved in controlling SOX9 expression [43]. Thus, we examined whether miR-27b enhanced SOX9 expression through the β-catenin pathway.…”
Section: Mir-27b Inhibits Hbmsc Hypertrophic Chondrocyte Differentiatmentioning
confidence: 99%
“…As a result, the survival of chondrocytes and their phenotypic stability and anabolic/catabolic balance activity are important for the maintenance of articular cartilage [27]. We further analyzed the changes of chondrocyte gene expression under the action of oligostilbenes, including matrix metalloproteinase 13(MMP13), an enzyme that is involved in the degradation of extracellular matrix (ECM) in OA [28]; COL2A1, the gene that provides type II collagen, which is the main protein in ECM of chondrocytes [29]; SOX9, an important factor in promoting cartilage differentiation, and its expression is decreased in OA patients [30]. We found that they all have the ability to inhibit the ECM degradation of chondrocytes and promote the expression of chondrocyte-specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…Pro‐inflammatory cytokines, such as IL‐1β and TNF‐α, contribute to a complex network of biochemical factors in chondrocytes to allot anabolism and catabolism (Fernandes et al., 2002). Sox9 and its downstream target Col2a1 are the master regulators to resist OA‐like changes (Hussain et al., 2018). Our results showed that TNF‐α combined with IL‐1β‐induced the down‐regulation of Sox9 and Col2a1 mRNA expression were reinforced in punicalin‐treated chondrocytes (Figure 4a,b).…”
Section: Resultsmentioning
confidence: 99%